Datasets for research on groundwater flow and its interactions with surface water in an alpine catchment on the northeastern Tibetan Plateau, China - Pan, Zhao; Ma, Rui; Sun, Ziyong; Hu, Yalu; Chang, Qixin; Ge, Mengyan; Wang, Shuo; Bu, Jianwei; Long, Xiang; Pan, Yanxi; Zhao, Lusong (2021)
Climate warming has significantly changed the hydrological cycle in cold regions, especially in areas with distributed permafrost. Groundwater flow and its interactions with surface water are important components of the hydrological process; however, few studies or modeling works have been based on long-term groundwater level, temperature, hydrogeochemistry or isotopic field observations from boreholes due to obstacles such as remote locations, limited infrastructure, and harsh work conditions. In the Hulugou catchment located in the headwater region of the Heihe River on the northeastern Tibetan Plateau (TP), we drilled four sets of depth-specific wells and monitored the dynamic groundwater levels and temperatures at different depths. Surface water (including river water, glacier meltwater, and snow meltwater), precipitation, groundwater from boreholes, spring water, and soil water samples were collected to measure the hydrochemistry, dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and stable and radioactive isotopes at 64 sites. This study provides datasets of these groundwater parameters spanning six consecutive years of monitoring/measurements. These data can be used to investigate the groundwater flow process and the interactions between groundwater and surface water on the TP under global climate change. The datasets provided in this paper can be obtained at https://doi.org/10.5281/zenodo.5184470 (Ma et al., 2021b) and will be subject to further updates.